MODERN PROBLEMS OF LABOR MANAGEMENT IN THE INDUSTRY OF UTILITIES AND THE WAYS OF THEIR SOLUTION - Elena V. Deryabina; Elena V. Dyakova (Наука Красноярья, 2021)
The authors of the article emphasize the increase of commercial interest in labor management in the field of housing and communal services as an element of stability of socio-technical and economic development of any organizations (enterprises).